2019
DOI: 10.1111/jne.12792
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural complications of sleep deprivation: Shedding light on the emerging role of neuroactive steroids

Abstract: Sleep deprivation (SD) is associated with a broad spectrum of cognitive and behavioural complications, including emotional lability and enhanced stress reactivity, as well as deficits in executive functions, decision making and impulse control. These impairments, which have profound negative consequences on the health and productivity of many individuals, reflect alterations of the prefrontal cortex (PFC) and its connectivity with subcortical regions. However, the molecular underpinnings of these alterations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 228 publications
(235 reference statements)
0
11
0
1
Order By: Relevance
“…Long working hours and high cognitive demand may lead to acute and chronic sleep deprivation in professional guards, drivers, military personnel, and healthcare workers, among others. Sleep deprivation increases response time to stimuli and lowers precision, as well as causing inattention, emotional lability, somnolence, and chronic fatigue 1 . A previous study has shown that a state of acute sleep deprivation (17-19 hours) has an equivalent effect as a serum level of 0.05% of alcohol and the response speeds were up to 50% slower for some cognitive tests and accuracy measures considered in many countries as incompatible with safe driving 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Long working hours and high cognitive demand may lead to acute and chronic sleep deprivation in professional guards, drivers, military personnel, and healthcare workers, among others. Sleep deprivation increases response time to stimuli and lowers precision, as well as causing inattention, emotional lability, somnolence, and chronic fatigue 1 . A previous study has shown that a state of acute sleep deprivation (17-19 hours) has an equivalent effect as a serum level of 0.05% of alcohol and the response speeds were up to 50% slower for some cognitive tests and accuracy measures considered in many countries as incompatible with safe driving 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The study shows potential mechanisms that underlie sex-related differences in behavior and its implications for stress-related illnesses. [199] Animal and human studies [210]…”
Section: Referencementioning
confidence: 99%
“…Neuroactive steroids (neurosteroids) are compounds synthesized de novo in neurons that modulate both gene expression and neuronal excitability, the latter through interactions with neurotransmitter receptors (for review, see Porcu et al, 2016 ; Paul et al, 2020 ). Neurosteroid levels in serum and brain are dysregulated in multiple psychiatric disorders (e.g., Rapkin et al, 1997 ; Brambilla et al, 2003 ; Hellgren et al, 2014 ; Frau et al, 2020 ; Hantsoo and Epperson, 2020 ). Moreover, allopregnanolone, a metabolite of progesterone and a GABAergic neurosteroid, has emerged as a clinically beneficial therapeutic ( Milivojevic et al, 2016 ; Bixo et al, 2017 ; Meltzer-Brody et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%